Ursolic acid ameliorates obesity of mice fed with high-fat diet via alteration of gut microbiota and amino acid metabolism - Tian, Chunfeng; Li, Jie; Bao, Yan; Gao, Long; Song, Lixin; Li, Kai; Sun, Ming (Frontiers in Microbiology, 2023)
Obesity has been regarded as one of the major health problems worldwide. Studies demonstrated that ursolic acid (UA) can significantly ameliorate the progress of obesity. However, whether the effect of UA on obesity depends on the regulation of gut microbiota and metabolism is uncertain. Here, we investigated the regulatory role of UA in obese mice from the perspective of intestinal microbiome and metabolomics analyses. The results demonstrated that UA treatment could reduce total triglyceride, total cholesterol, and low-density lipoprotein cholesterol levels in serum and inhibit liver-lipid accumulation in obese mice. The results of the gut microbiota analysis showed that UA intervention could shift the Firmicutes to Bacteroidetes ratio at the phylum level and increase in the genera of Lactobacillus, Bacteroides, and Akkermansia. Additionally, metabolomics analysis showed that the beneficial influence of UA on obesity partly depended on amino acid metabolism. The current study demonstrated the roles of UA in the anti-obesity process, which partly depends in part on alterations in the gut microbiota and metabolism. Therefore, our findings highlight the potential therapeutic effect of UA on the improvement of diet-induced obesity in humans.